A system dynamics based simulation model to evaluate regulatory policies for sustainable transportation planning. (2nd January 2017) - Sayyadi, Reza; Awasthi, Anjali
Abstract: Transportation is a major source of energy consumption and emission generation. To limit the negative environment impacts arising from transportation of goods and people, several initiatives and policies are being put in place by municipal administrators, local governments, and federal governments. Since transportation is a dynamic system in which the individual components and their interactions are changing over time, decision-makers need efficient approaches to investigate system behavior and devise sustainable transportation policies for the benefit of city, its residents, and their environment. In this paper, we propose a system dynamics-based simulation model to evaluate the impact of regulatory policies for sustainable transport planning. Causal loop diagrams are developed to investigate transportation system elements, their inter-relationships, and evolution of behavior over time. A numerical study for vehicle trip reduction is provided. The results of our simulation study reveal that trip-sharing policy effectively decreases congestion while car ownership decreases tendency of vehicular trips and increases public transit trips.